The Role of PJOK Teacher in Preventing the Transmission of Covid 19 at SD Inpres Nggemo, Maukaro District Ende District - Rawe, Aschari Senjahari; Sola, Heribertus Sawa (Edumaspul: Jurnal Pendidikan, 2023)
The problem in this research is the effort to prevent Covid-19 at SD Inpres Nggemo and what is the role of PJOK teachers in preventing transmission of Covid-19 at SD Inpres Nggemo, Maukaro District. Nggemo, Maukaro District. The approach that the researcher uses in this study is qualitative, namely an approach that tries to understand the individual meaning of the subject under study. The subjects of this study consisted of informants, namely PJOK teachers and students at SD Inpres Nggemo, Maukaro sub-district. In obtaining the data, the researcher used interview, observation and documentation techniques.The results of this study indicate that the role of the PJOK teacher at SD Inpres Nggemo during this pandemic is very good, because not only as a teacher but the role of the PJOK teacher as a facilitator who must provide learning motivation for students so that students remain enthusiastic in participating in learning at school by complying with the protocol. health during the Covid-19 pandemic.